1966
DOI: 10.1104/pp.41.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethylene on Auxin Transport

Abstract: Summary. The effect of ethylene on the uptake, distribution and polar transport of Cl4 from indole-3-acetic acid-2-C'4 and naphthalene acetic acid-i-C'4 in tissue sections was studied. Test species were cotton (Gossypiumn hirsutumit, L.) and cowpea (Vignla sinlellsis, Endl.). Generally, incubation of tissue or initact plants with ethylenie reduced the degree of polar auxin transport. Ethylene inhibited the movemiient of both auxins in stem tissue and IAA in petiole tissue of cotton. The effect of ethylene onl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
84
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 20 publications
6
84
0
Order By: Relevance
“…This is true since ethylene was shown to have an effect on auxin molecules in transit completely separated from the cut surface. Al-though earlier studies have shown an effect of ethylene on extractable unlabeled auxin (10,12) and on the amount of 14C transported from labeled auxin (2,6,13,14,15), they have not shown the contribution which the cut surface makes to these ethylene effects.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is true since ethylene was shown to have an effect on auxin molecules in transit completely separated from the cut surface. Al-though earlier studies have shown an effect of ethylene on extractable unlabeled auxin (10,12) and on the amount of 14C transported from labeled auxin (2,6,13,14,15), they have not shown the contribution which the cut surface makes to these ethylene effects.…”
Section: Discussionmentioning
confidence: 96%
“…Stem sections excised from plants treated with ethylene often accumulate 14C at or near the apical cut surface to a much greater extent than untreated sections (2,13,14). This accumulation of 14C SUggests that a rapid binding, conjugation or breakdown of auxin (see Review,11) may take place at the cut surface resulting in an apparent reduction of auxin transport.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7), but some inhibition of NAA uptake was observed. Pretreatment with ethylene also inhibited auxin uptake by cotton and cowpea petiole segments (25).…”
Section: Methodsmentioning
confidence: 99%
“…If the ethylene attachment site were similar for all of the above processes, the initial reaction of different kinds of cells to the gas probably would also be similar. A number of initial reactions to ethylene presently being considered include alteration of membrane permeability (18), regulation of auxin activity (10,21), and regulation of nucleic acid metabolism (16).…”
mentioning
confidence: 99%